Transient Hyperthyroidism following the ingestion of complementary medications containing kelp seaweed: A case-report. Issue 37 (September 2019) - Gherbon, Adriana; Frandes, Mirela; Lungeanu, Diana; Nicula, Marioara; Timar, Romulus
Abstract: Rationale: The prevalence of obesity has increased over the past few years, becoming a public health problem. Generally, the primary therapeutic remedies are diet, physical exercise, medication, and bariatric surgery. However, an increased number of obese and overweight people are using complementary and herbal slimming supplements. Patient concerns: A 70-years-old Caucasian woman presented to the outpatient clinic with tachycardia (>100 bpm), insomnia, anxiety, and recent weight loss (6 kilos in 3 months). She had no previous thyroid disease, but she presented transient hyperthyroidism at 3 months after ingestion of tablets containing kelp seaweeds. Diagnoses: Hypertensive and obese patient, without previous thyroid disease, presented with transient hyperthyroidism at 3 months following ingestion of tablets containing kelp seaweed. Interventions: The kelp-containing tablets were discontinued, and antithyroid therapy with Methimazole was initiated as follows: Methimazole at 15 mg/day for 1 month, at 10 mg/day in the second month, and 5 mg/day for the third month. Outcomes: After 3 months of antithyroid therapy and without the consumption of kelp - containing tablets, normal thyroid function was regained. Further analysis revealed normal thyroid function, so the hyperthyroidism reversed completely. Lessons: Adults who consume complementary medication based on kelp seaweed should be informed of the risk of developing thyroid dysfunction also in the absence of any pre-existing thyroid disease. Due to the high iodine content, supplements containing kelp should be taken with the supervision of a physician and with monitoring of thyroid function.